Regionale Migration in Abhängigkeit von Humankapital und sektoraler Struktur: Eine empirische Analyse am Beispiel von Deutschland und Polen - Alexander Kubis (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
Ostdeutschlands Regionen stellen als Bindeglied zwischen dem westlichen Europa und den mittel- und osteuropäischen Ländern für die Regionalforschung ein interessantes Forschungsobjekt dar. Hierbei ist es von herausragendem Interesse, inwieweit sich die ostdeutsche Abwanderung nach Westdeutschland abschwächt, beziehungsweise ob der Osten an dem zu erwartenden Migrationsstrom aus Osteuropa partizipiert. Gerade aus Polen, dem direkten Nachbarn und sechstgrößten Land der EU, werden starke Migrationsströme erwartet. Bereits im Falle der deutschen Binnenmigration bestehen starke strukturelle Unterschiede zwischen Ost- und Westdeutschland, welche durch bestehende makroökonomische Erklärungsansätze bisher nicht vollständig erfasst werden. Die Analyse der Komplexität individueller Entscheidungsprozesse, welche sich letztlich hinter den empirisch beobachtbaren interregionalen Migrationsströmen verbergen, ist der Schlüssel zum besseren Verständnis einer künftigen räumlichen Entwicklung ... – – As a link between Eastern and Western European countries East German regions represent an interesting field for regional research. Predicting the East German outmigration to West Germany and the potential migration gains from Eastern Europe is of general interest for regional policy in East Germany. Strong migration gains are expected particularly from Poland, the direct neighbour of East Germany and the sixth-largest EU country. Even in case of German internal migration, existing empirical analyses at the macrolevel do not fully reflect the significant structural differences between both parts of the country. Understanding future spatial development requires an analysis of the complex individual decision processes behind the observed aggregated inter-regional migration flows. The theory on human capital predicts that job changes between occupations require investments in occupation-specific knowledge. Thus, regional differences in occupational structure should affect income expectations for the region of destination. The thesis approximates the human capital investments required through differences in gross value added per worker between sectors and regions of origin and destination. While previous macroeconometric models of migration control for several regional determinants, they have so far neglected the effects of human capital investments. The thesis proposes a method to implement human capital as a determinant of migration flows between German NUTS 3 regions. The results indicate that expected required investments in human capital reduce regional migration ...
urn:nbn:de:gbv:3:2-23544
Keywords: 330; regionale Migration; Humankapital; sektorale Struktur; Deutschland; Polen; Arbeitsmarktmobilität; Prognose; regional migration; human capital; sectoral structure; Germany; Poland; labour mobility; forecast